Heterozygous mutations in ERF cause syndromic craniosynostosis with multiple suture involvement. (22nd June 2015) - Chaudhry, Ayeshah; Sabatini, Peter; Han, Liping; Ray, Peter N.; Forrest, Christopher; Bowdin, Sarah
<x xml:space="preserve">Abstract</x> Craniosynostosis is a clinically and genetically heterogeneous condition. Knowledge of the specific genetic diagnosis in patients presenting with this condition is important for surgical and medical management. The most common single gene causes of syndromic craniosynostosis are mutations in FGFR1, FGFR2, FGFR3, TWIST1, and EFNB1. Recently, a new single gene cause of craniosynostosis was published, together with phenotype data that highlight the clinical importance of making this specific molecular diagnosis. Phenotypic features of "ERF‐related craniosynostosis" include sagittal or multiple‐suture synostosis, Chiari malformation, and language delay. In order to determine the contribution of ERF mutations to genetically undiagnosed patients with craniosynostosis, we sequenced the coding regions of ERF in 40 patients with multi‐suture or sagittal suture synostosis. We identified heterozygous ERF mutations in two individuals (5%). One mutation positive individual had pansynostosis, while the second had bilateral coronal and metopic synostosis. Both presented in infancy or childhood (age 3 months, and 6 years 9 months, respectively). One had CNS abnormalities including Chiari I malformation. Dysmorphic features included hypertelorism, proptosis, depressed nasal bridge, and retrognathia, in keeping with previously reported cases. The individuals did not require repeated cranial surgeries. ERF‐related craniosynostosis should be suspected in patients presenting with multiple suture or sagittal synostosis. © 2015 Wiley Periodicals, Inc.